2017
DOI: 10.2147/vhrm.s135308
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pain during endovenous laser ablation of the great saphenous vein with ultrasound-guided femoral nerve block

Abstract: BackgroundEndoluminal laser ablation is now considered the method of choice for treating greater saphenous vein insufficiency. General anesthesia and peripheral nerve blocks with sedation have the risk of post-procedural delay in discharge and prolonged immobilization with the risk of deep vein thrombosis. The main pain experienced by patients during the procedure is during the laser ablation and the multiple needle punctures given along and around the great saphenous vein. The aim of our study was to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“… 58 , 59 Endovenous laser ablation is also described as an indication for femoral nerve block. 60 , 61 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 58 , 59 Endovenous laser ablation is also described as an indication for femoral nerve block. 60 , 61 …”
Section: Resultsmentioning
confidence: 99%
“…The majority of femoral nerve blocks used ultrasound guidance (22 studies), 23 , 26 , 28 , 29 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 39 , 42 , 47 , 48 , 49 , 54 , 56 , 57 , 59 , 60 , 61 but 10 studies used nerve stimulation, 22 , 27 , 34 , 40 , 41 , 44 , 45 , 46 , 50 , 52 and eight studies did not report the nerve identification technique or were not clear in their description. 24 , 25 , 38 , 43 , 51 , 53 , 55 , 58 …”
Section: Resultsmentioning
confidence: 99%
“…[11] Dzieciuchowicz et al [12] used femoral nerve block with 20 mL of 1% lidocaine in addition to TA in one of the two different groups who underwent endoluminal laser ablation and tumescent ablation in the other, and reported that pain intensity and need for TA solution were lower in the group they added femoral nerve block. Al Wahbi [13] also reported that femoral nerve block added to TA during endoluminal laser ablation decreased pain intensity without affecting the surgical duration. As the target nerve was completely localized with ultrasonography and a mixed solution was used in our study, a total volume of 20 mL was sufficient in the femoral nerve group without the need for relatively high local anesthetic injections used for TA, and surgical duration was not affected and no additional analgesia was needed.…”
Section: Discussionmentioning
confidence: 95%
“…Для обезболивания ЭВЛО, РЧА и мини-флебэктомии применяется тумесцентная анестезия, для стриппинга -проводниковая анестезия, хотя возможна и комбинация этих видов анестезии [1][2][3][4][5]. Проводниковая анестезия -это обратимая блокада передачи нервного импульса по крупному нервному стволу (нерв, сплетение, узел) путем введения раствора местного анестетика в параневральное пространство.…”
Section: амбулаторная анестезияunclassified